Integrating traditional wisdom and modern strategies: Prophet Yusuf's Legacy and SDG 2 - Nurul Ilyana Muhd Adnan,; Mohd 'Adli Zahri,; Mohamad Shaharudin Samsurijan,; Zahri Hamat, (Penerbit Universiti Kebangsaan Malaysia, 2024)
This study aims to explore the enduring relevance of Prophet Yusuf's ancient strategies for resource management and equitable distribution within the context of modern efforts to ensure food security and promote sustainable agricultural practices. This study utilizes a qualitative content analysis methodology, analyzing primary sources, such as religious texts recounting the story of Prophet Yusuf, alongside secondary sources, including academic articles, policy documents, and reports on sustainable agriculture and food security. The findings reveal that Prophet Yusuf's strategies - specifically his anticipatory planning and equitable resource distribution - hold significant relevance for modern agricultural practices and policymaking. The analysis demonstrates that integrating these ancient strategies with modern technologies and sustainable agricultural practices can significantly contribute to achieving SDG 2. This study advocates blending traditional insights with modern science to improve food security and agriculture, urging policymakers to focus on foresight and equity, and encouraging farmers to adopt Yusuf-inspired sustainable practices, all aimed at fulfilling SDG 2's vision of a hunger-free future.